Changes in sleep quality of children with epilepsy and anxiety of their caregivers after COVID-19 infection: a case-series report - Li, Dan; Shi, Yongjing; Wang, Bo; Zhou, Jing; Wang, Xueying; Huang, Shaoping; Yang, Lin (Frontiers in Pediatrics, 2023)
Objective To study the changes in epileptic seizures and sleep quality in children with epilepsy (CWE) and the changes in anxiety of their caregivers after infection with COVID-19. Methods Outpatients and inpatients of CWEs were selected as subjects and a questionnaire survey was used to carry out this case-series study. The demographic information of the CWEs and their caregivers, information about epilepsy, and information about the vaccination, infection, and treatment of COVID-19 were collected. The changes in sleep quality of CWEs and the changes in anxiety of their caregivers were assessed by the Child Sleep Habits Questionnaire (CSHQ) and Caregiver Anxiety Scale (CAS). Risk factors affecting sleep habits in CWEs and caregiver anxiety were further analyzed by one-way analysis of variance. Results A total of 312 children were included in the study. Among them, 134 patients (42.9%) were female. The average age of the children was 9.30 ± 3.88 years, and the duration of epilepsy was 4.59 ± 3.36 years. A total of 221 of the 312 children were infected with COVID-19, and all the infected children developed fever, which lasted for 1.71 ± 1.13 days. 10 children were satisfied with controlled seizures for more than 1 year and relapsed after COVID-19 infection (4.2%), 4 cases (3.6%) with increased seizures, and 8 children with reduced seizures (7.7%), 17 children (7.7%) had no change in seizures, and 182 children (82.3%) remained seizure-free after the COVID-19 infection. The average sleep time of the CWEs was 9.25 ± 1.04 h and the average total score of the CSHQ was 37.25 ± 5.19, among which 44 cases (14.1%) had more than 41 points. As the result of the CAS, 16 of them (5.13%) scored above 50 and the average total score was 31.49 ± 8.09. The control of seizures, age of onset, types of anti-seizure medicines (ASMs), and seizure duration were risk factors affecting sleep quality. Accordingly, the score of CAS was significantly lower when there was more than one caregiver who cared for the CWE. Conclusions COVID-19 infection did not cause an increase in seizures in CWEs, nor did it worsen their sleep quality of them or aggravate the anxiety of their caregivers.